Analisis Makna Denotasi dan Konotasi Pada Lirik Lagu ‘Atemlos Durch Die Nacht’ Karya Helene Fischer - Noya van Delzen, June Carmen; Wenno, Eldaa Crystle; Soumokil, Piet (J-EDu: Journal - Erfolgreicher Deutschunterricht, 2025)
This study aims to analyze the denotative and connotative meanings found in the lyrics of the song “Atemlos durch die Nacht” by Helene Fischer. A song is an effective medium for conveying messages and emotions through a combination of melody and lyrics. The lyrics of “Atemlos durch die Nacht” were chosen because of their deep emotional expression and the song’s historical significance as one of Germany’s most successful songs. The research employs a qualitative descriptive method focusing on semantic analysis to identify the literal (denotative) and implied (connotative) meanings in each line of the song’s lyrics. Data were collected through document analysis, and each lyric was interpreted according to its contextual meaning. The findings show that each lyric of the song contains both denotative and connotative meanings that express feelings of freedom, love, and enthusiasm. The denotative meanings present the literal interpretations of the words, while the connotative meanings reveal emotional and symbolic associations related to human experiences of joy, affection, and liberation. In conclusion, the study highlights that linguistic elements in song lyrics can serve as powerful tools for expressing human emotions and cultural values through layers of meaning.